Value-added food applications utilizing emerging commodities (sorghum, sorghum processing byproducts, Camelina sativa) that support sustainable agricultural practices - Kaya, Eda Ceren (Kansas State University, 2023)
Emerging commodities such as sorghum (Sorghum bicolor L. Moench), Camelina sativa (Camelina sativa L.), and renewable resources of distillers’ dried grains with solubles (DDGS) from ethanol fermentation possess high potential to be utilized in new and value-added food applications. Sorghum (Sorghum bicolor L. Moench) is the third commonly grown cereal crop in the United States (USA) and the fifth in the world. It is recognized as a sustainable crop due to its high drought tolerance and quicker adaptability to various environments. There is, therefore, a growing interest in expanding the utilization of sorghum and its byproducts in support of sustainable agricultural practices. In addition to this, DDGS offers great potential as a renewable source for manufacturing biodegradable packaging film materials due to its high protein and fiber content. Sorghum and sorghum DDGS can be utilized to manufacture resin-like viscous materials and biodegradable packaging films. In addition to this, the emerging oil seed crop Camelina sativa has great potential to be used as novel additives for various food applications. It has been transgenically engineered to produce high levels of acetyl-TAG by introducing acetyl-transferase enzymes from different Euonymus species. The unusual acetyl-TAG molecules obtained from transgenic Camelina sativa seeds can be used to improve the functional properties of biodegradable packaging films as a plasticizer and to increase the stability and capacity of protein foams and emulsions as an emulsifier or a stabilizer. The first objective is to develop a biodegradable packaging film using sorghum DDGS and to characterize the effects of milling pretreatment and suitable solvents on physical, mechanical, and thermal properties. In this objective, the films were prepared from sorghum DDGS after Udy and Colloid milling and solubilized using water, chloroform (1:0, 1:1, 1:2, 0:1 (v/v) water: chloroform ratio) and ethanol. The lowest (P < 0.05) moisture solubility (21.19 ±0.03%) and the highest tensile strength (19.19 ± 0.03 MPa) were obtained when Udy milling was applied to DDGS using a 1:2 ratio. The melting temperature of the films significantly (P < 0.05) increased (134.01± 1.1 °C) when DDGS was pretreated using dry milling with the combined use of water, chloroform, and ethanol as compared to only water for solubilization. Overall, dry, and wet milling with a suitable solvent ratio improved film properties. The second objective is to improve the functional properties of DDGS films by the presence of the sn-3 acetyl group of acetyl TAG, obtained from transgenic Camelina sativa, and preconditioning via wet milling and suitable solubilization. The 3-acetyl-1,2-diacyl-sn-glycerols (acetyl-TAGs) are unusually structured triacylglycerol (TAG) molecules that possess an sn-3 acetate group instead of a long chain fatty acid. This reorganized structure enables Acetyl-TAG to possess different physical properties from regular TAG, including reduced viscosity and improved cold temperature properties. Therefore, high oleic acetyl-TAG from engineered form Camelina seeds can be used as a novel and high-yield plasticizer. The moisture solubility of the films pretreated via a ball mill and solubilized with a 1:1 (v/v) solvent ratio decreased by 9% when acetyl-TAG concentration increased from 0.1% to 0.2% (w/v). The elongation at the break increased by 24% when 0.2% (w/v) acetyl-TAG was incorporated into the film prepared with the same conditions as compared to the film without acetyl-TAG. The addition of acetyl-TAG also reduced the wettability and improved the hydrophobic character of the films. Overall, acetyl-TAG with wet milling improved the film properties. The third objective of this dissertation is to use acetyl-triacylglycerols (acetyl-TAG) that possess sn-3 acetate group with high oleic content as an effective stabilizer to the foam at reduced sugar concentrations by increasing the surface viscosity and minimizing foam serum drainage. A fractional factorial Box-Wilson design was used to investigate the effects of whey protein concentration (WPI) (2-10 wt%), sucrose concentration (SC) (10-30 wt%), and acetyl-TAG concentration (ATC) (0-1 wt%) on overrun (FO), stability against serum drainage (FD) and surface dilatational rheology. Each response was analyzed by linear regression model fitting and a backward elimination algorithm for significance ([alpha] = 0.01). FO was significantly affected (P<0.01) by WPI and ATC, but not sucrose concentration. The optimum overrun (nearly 700%) was obtained at 9 wt% WPI and 0.6 wt% ATC. Drainage and viscoelastic properties were significantly (P<0.01) affected by all process variables. Dynamic complex modulus (|E|) as measured using an optical tensiometer was around 30-40 mN/m when acetyl-TAG was higher than 0.5 wt%. Our findings indicated that the acetyl-TAG can be used to enhance the stability of protein foams in reduced sugar food products, but not at high sugar concentrations (30 wt%). The fourth objective of this study is to increase emulsion and foam stability at low saturated oil in water emulsions before and after whipping via wild-type acetyl-TAG. In this study, protein-stabilized emulsions using whey protein hydrolysate (WPH) (2.5 % (w/v)), coconut oil (15% (w/v) and 30% (w/v)) and wild-type acetyl-TAG (0, 0.5, 1 % (w/v) were prepared by a high-pressure homogenizer. Particle size, creaming index, and overrun were used to evaluate the stability and foaming ability of whipped emulsion during aging (21 days at 25°C). Furthermore, the percentage of adsorbed protein, zeta potential, and interfacial rheology were analyzed to investigate the effect of acetyl-TAG on the stability of WPH at the oil-water interfaces and the interaction between acetyl-TAG and coconut oil phase and protein at the interfacial level. The results showed that acetyl-TAG significantly (P <0.05) reduced the particle size and the particle size decreased (P<0.05) further with an increase in the concentration of acetyl-TAG from 0.5% to 1% (w/w) whereas the creaming index decreased (P < 0.05) using acetyl-TAG in emulsion preparation. Furthermore, the capacity (overrun%) of whipped emulsions significantly (P<0.05) increased and drainage of whipped emulsions significantly (P<0.05) reduced with the addition of acetyl-TAG. In conclusion, wild-type acetyl-TAG may be used as an effective surfactant in emulsions stabilized by WPH and improve the whipping characteristics of aerated emulsion systems. The fifth objective of this dissertation is to obtain oleoresins from waxy burgundy sorghum grain and to characterize the effects of the extraction process and solvents on their composition and functional properties. Oleoresins were obtained by using the following solvents with and without ball milling: two types of novel ionic liquids (IL₁: 1-n-Hexyl-3-methylimidazoliumchloride, IL₂: 1-Ethyl-3-methylimidazoliumchloride), ethanol and dichloromethane. The effects of processing were evaluated for the extraction yield, protein, fat, and total phenolic content, fatty acid composition, particle size and zeta potential, and FTIR spectra. The use of ILs and the ball mill process significantly (P < 0.05) affected the extraction yield and physicochemical properties. The highest extraction yields increased (31.35% ± 0.58) when ball milling was used with IL₂ in comparison to the lowest (18.37% ± 0.77) obtained by traditional ethanol extraction. Similarly, protein concentration and phenolic content were the highest (1.37% ± 0.05 and 0.57% ± 0.01, respectively) with ball milling extraction and IL₁. The FTIR spectra indicated higher phospholipids (at 1200 cm⁻¹) and protein-phospholipid bonding (at 1700 cm⁻¹) by ILs, and ball milling as compared to traditional extraction. Overall, wet milling-assisted extraction by using a ball mill and ILs provided control over the composition of the oleoresins important for value-added food applications and higher extraction efficiencies as compared to traditional techniques. This study showed the oleoresins offering great potential for value added food applications can be successfully extracted with high extraction efficiency from waxy burgundy whole grain sorghum and their composition can be controlled via wet milling-assisted extraction using a ball mill and novel ionic liquids (ILs). Additionally, renewable biodegradable packaging film alternatives can be manufactured from sorghum DDGS by dry and wet milling preconditioning with a suitable solubilization technique. Furthermore, high oleic acetyl-TAG from engineered form Camelina seeds can be used as a novel and high-yield plasticizer to improve the physical, mechanical, and surface hydrophobicity of DDGS films. Moreover, acetyl-TAG isolated from transgenic Camelina sativa seeds with high oleic content can serve as an effective protein foam stabilizer at reduced sugar concentrations. Similar to this, wild-type acetyl-TAG can effectively assist whey protein hydrolysate to stabilize coconut oil-based emulsions and promote interfacial adsorption.
Keywords: Sorghum; Distillers dried grain with solubles; Biodegradable packaging film; Sorghum oleoresin; Camelina sativa